Epithelial–Mesenchymal Interactions in Fibrosis and Repair. Transforming Growth Factor-β Activation by Epithelial Cells and Fibroblasts - Sheppard, Dean (Ann Am Thorac Soc, 2015)
Transforming growth factor-β (TGF-β) plays a central role in driving tissue fibrosis. TGF-β is secreted in a latent form, held latent by noncovalent association of the active cytokine with a peptide derived from cleavage of the N-terminal domain of the same gene product, and needs to be activated extracellularly to exert any of its diverse biological effects. We have shown that two of the three mammalian isoforms of TGF-β, TGF-β(1) and TGF-β(3), depend on interactions with cell surface integrins for activation. We found that the integrin αvβ(6) is highly induced on injured alveolar epithelial cells, potently induces TGF-β activation, and is critical for the development of pulmonary fibrosis and acute lung injury. However, although TGF-β drives fibrosis in virtually every anatomic site, αvβ(6)-mediated TGF-β activation is much more restricted. For example, αvβ(6) is not induced on injured hepatocytes and plays little or no role in cirrhosis induced by repetitive hepatocyte injury. Fibroblasts are highly contractile cells that express multiple integrins closely related to αvβ(6), which share the promiscuous αv subunit, so we reasoned that perhaps one or more of these αv integrins on fibroblasts might substitute for αvβ(6) and activate the TGF-β required to drive liver fibrosis. Indeed, deletion of the αv subunit from activated fibroblasts protected mice from carbon tetrachloride–induced liver fibrosis. Importantly, these same mice were protected from bleomycin-induced pulmonary fibrosis and renal fibrosis caused by unilateral ureteral obstruction, despite the presence of epithelial αvβ(6) in these mice. These results suggest that the generation and maintenance of sufficient quantities of active TGF-β to cause tissue fibrosis in multiple organs probably depends on at least two sources—TGF-β activation by injured epithelial cells that drives fibroblast expansion and activation and an amplification step that involves TGF-β activation by an αv integrin on activated fibroblasts. These results suggest that intervening at either of these steps could be useful for the treatment of fibrotic diseases.